Absorption of CO2 in aqueous solutions of 2-methylpiperidine: Heats of solution and modeling. (April 2016) - Coulier, Y.; Lowe, A.; Tremaine, P.R.; Coxam, J.-Y.; Ballerat-Busserolles, K.
Highlights: Absorption of CO2 in 2-methylpiperidine solutions was studied. Thermodynamic model shows good agreement with experimental results. Energetic contributions taking place during the dissolution process are described. Abstract: Absorption of CO2 in aqueous solutions of 2-methylpiperidine has been studied at different temperatures, pressures and amine compositions. The enthalpies of solution for carbon dioxide in aqueous solutions of 2-methylpiperidine were measured using a flow calorimetric technique and gas solubility limits were simultaneously estimated from the calorimetric data. A rigorous thermodynamic model of phase equilibria based on a γ–ϕ approach was used to represent the absorption of CO2 in aqueous solutions of 2-methylpiperidine. The model interaction parameters were adjusted using the experimental enthalpies of solution and vapor–liquid equilibrium data.